Ginsenoside Rg1 attenuates LPS-induced cognitive impairments and neuroinflammation by inhibiting NOX2 and Ca2+–CN–NFAT1 signaling in mice. (December 2021) - Dong, Xianan; Li, Lan; Zhang, Duoduo; Su, Yong; Yang, Liu; Li, Xuewang; Han, Yuli; Li, Weiping; Li, Weizu
Graphical abstract: Highlights: Rg1 improved LPS-induced cognitive impairments and neuronal damage. Rg1 ameliorated LPS-induced NLRP1 inflammasome activation and synaptic dysfunction. Rg1 decreased excess ROS production and NOX2 expressions in LPS-induced mice. Rg1 suppressed LPS-induced calcium homeostasis disorder and CN-NFAT1 activation. Abstract: The levels of lipopolysaccharide (LPS) are increased in the brain and blood of Alzheimer's disease (AD) patients and contribute to neuroinflammation and neurodegeneration in AD. Ginsenoside Rg1 (Rg1) is reported to possess neuroprotective effects on neurodegenerative diseases by improving oxidative stress and inflammation. However, the protective effect and mechanism of Rg1 in neuroinflammation and neuronal damage in LPS-induced mice remain unclear. In this study, the results demonstrated that exposure to LPS for 14 days significantly induced cognitive impairment, neuronal injury and NLRP1 inflammasome activation, significantly increased ROS generation and NADPH oxidase 2 (NOX2) expression and elevated the levels of p-PLC, calcineurin (CN) and nuclear factor of activated T cells 1 (NFAT1) in the hippocampus. Treatment with Rg1, tempol (a superoxide dismutase mimic) and apocynin (an inhibitor of NOX) significantly improved cognitive impairment and neuronal damage, inhibited the activation of NLRP1 inflammasome, reduced ROS generation and NOX2 expression and decreased the levels of p-PLC, CN and NFAT1 in the hippocampus. Additionally, the calcium imaging results suggested that Rg1 administration significantly inhibits [Ca 2+ ]i overload and maintains calcium homeostasis in LPS-induced HT22 cells. These results suggest that Rg1 treatment can improve LPS-induced activation of the NLRP1 inflammasome and neuronal damage through inhibiting NOX2, [Ca 2+ ]i overload and CN-NFAT1 activation.